Inhibition of CRISPR-Cas12a trans-cleavage by lead (II)-induced G-quadruplex and its analytical application. (1st June 2022) - Yu, Ying; Li, Wenhui; Gu, Xinzhe; Yang, Xiaojun; Han, Yiyi; Ma, Yingqing; Wang, Zhengwu; Zhang, Juan
Highlights: The inhibitory effect of Pb 2+ -induced G-quadruplex on CRISPR-Cas12a trans cleavage has been investigated. A simple fluorescence resonance energy transfer method has been explored to detect Pb 2+ . The method can be successfully applied to analyze Pb 2+ in tea drink and milk. Abstract: In this work, the inhibition of clustered regularly interspaced short palindromic repeats (CRISPR) - CRISPR associated protein (Cas) trans-cleavage by Pb 2+ -induced G-quadruplex has been firstly explored to detect Pb 2+ in tea beverage and milk. In absence of Pb 2+, the Na + -induced G-quadruplex can be cleaved by CRISPR-Cas12a. In contrast, Pb 2+ can competitively combine with G-quadruplex, resulting in its conformational changes and resistance to trans-cleavage of CRISPR-Cas12a. Therefore, the fluorescence resonance energy transfer can happen. Pb 2+ can be detected in a linear range from 100 nM to 5 µM with a lowest detection limit of 2.6 nM and a relative standard deviation of 4.32%. In summary, this work not only provides a new method for Pb 2+ detection based on its induced G-quadruplex inhibition on CRISPR-Cas12a trans-cleavage, but also broadens the application of CRISPR-Cas system for heavy metal analysis in the field of food safety.